If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 5y) = 12 (4x * 3 + 5y * 3) = 12 (12x + 15y) = 12 Solving 12x + 15y = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15y' to each side of the equation. 12x + 15y + -15y = 12 + -15y Combine like terms: 15y + -15y = 0 12x + 0 = 12 + -15y 12x = 12 + -15y Divide each side by '12'. x = 1 + -1.25y Simplifying x = 1 + -1.25y
| sqrt(x^2-3x)=2 | | -6+7(x-3)=37-x | | .08(x)+.12(x+250)=348 | | x+0.13x=3500 | | X^2-18x-31=0 | | 28=4/3w | | -7(-5k-8)=196 | | 24/0.3 | | 2f+3w=15.55 | | -272=3n-7(8n+1) | | 0.7z-3=0 | | 3.5+46.9*x-9.8*x^2=0 | | 6+3x=8+11 | | 1404=.02(x) | | 14M-28=4(M+3) | | 3y=28-4y | | X/3=x-31/2 | | (3x^5-2x^3+4)+(x^4+2x^3-7)= | | 2y-2/5=-1/3 | | 8(3a+6)=9(2a-3)-9 | | 5-(2x+4)=15 | | -8(-x-7)=-x+29 | | 24y-20x=72 | | 1404=.08(x)+.04(y) | | 4(x+1)=2(x+3)-4 | | Z^2=8+6i | | 11-w=187 | | 4x+1=3(x+2)+2x | | 20.44=1.5x*x | | 2n^2+3x-9=0 | | 20x-5y=1.2 | | 0=1.5x*x |